2006
DOI: 10.1095/biolreprod.105.049304
|View full text |Cite|
|
Sign up to set email alerts
|

Lipid Remodeling of Murine Epididymosomes and Spermatozoa During Epididymal Maturation1

Abstract: We have isolated vesicular structures from mouse epididymal fluid, referred to as epididymosomes. Epididymosomes have a roughly spherical aspect and a bilayer membrane, and they are heterogeneous in size and content. They originate from the epididymal epithelium, notably from the caput region, and are emitted in the epididymal lumen by way of apocrine secretion. We characterized their membranous lipid profiles in caput and cauda epididymidal fluid samples and found that epididymosomes were particularly rich in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
2
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(196 citation statements)
references
References 60 publications
10
168
2
12
Order By: Relevance
“…In other cell systems, exosomes are usually formed in the endosomal compartments that contain multivesicular bodies which then fuse with the plasma membrane to release the vesicles (Yanez-Mo et al, 2015). Larger vesicles up to 1000 nm have also previously been described in the rodent epididymal lumen, as were multivesicular bodies, suggesting there may be several populations of extracellular vesicles in the epididymal lumen that are released from distinct cell types by different mechanisms and that this may vary between species (Rejraji et al, 2006;Caballero et al, 2013). Our studies showing that the apical bleb in narrow/apical cells contained the tetraspanin CD9, a marker for exosomes and that CD9 positive vesicles were observed distal to the intermediate zone suggests that narrow/apical cells may also release exosomes but possibly by the more conventional mechanism involving endosomes and multivesicular bodies and that these vesicles in the epididymis may be larger in size.…”
Section: Cres Subgroup Members Are In Extracellular Vesiclesmentioning
confidence: 76%
“…In other cell systems, exosomes are usually formed in the endosomal compartments that contain multivesicular bodies which then fuse with the plasma membrane to release the vesicles (Yanez-Mo et al, 2015). Larger vesicles up to 1000 nm have also previously been described in the rodent epididymal lumen, as were multivesicular bodies, suggesting there may be several populations of extracellular vesicles in the epididymal lumen that are released from distinct cell types by different mechanisms and that this may vary between species (Rejraji et al, 2006;Caballero et al, 2013). Our studies showing that the apical bleb in narrow/apical cells contained the tetraspanin CD9, a marker for exosomes and that CD9 positive vesicles were observed distal to the intermediate zone suggests that narrow/apical cells may also release exosomes but possibly by the more conventional mechanism involving endosomes and multivesicular bodies and that these vesicles in the epididymis may be larger in size.…”
Section: Cres Subgroup Members Are In Extracellular Vesiclesmentioning
confidence: 76%
“…During epididymal transit (7 dpt) sperm plasma membrane undergoes substantial remodeling (Dacheux et al, 2005) and mouse epididymal spermatozoa are characterized by high percentages of sphingomyelin and PUFA, mainly arachidonic, docosapentanoic and docosahexanoic acids that confer fluidity to sperm membranes (Rejraji et al, 2006). In addition, considering that most of sperm functions required for fertilization are developed in the epididymis, such as motility, zona binding and membrane fusion abilities (Cooper, 2007), it is not far fetched to hypothesize that a disturbed maturation of epididymal spermatozoa by Me-Pa exposure could impact their fertilizing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…These changes were also associated with a reduction in motility percentage and appearance of abnormal sperm morphology. In an attempt to explain the mechanism by which hypercholesterolaemia produced deleterious effects on male fertility, Rejraji et al [21] reported that lipid homeostasis is of particular importance in germ cells. These cells undergo different modifications in lipid concentrations, especially cholesterol, desmosterol and phospholipids during their differentiation.…”
Section: Discussionmentioning
confidence: 99%